EFFECT OF 6 WEEKS OF ROPE TRAINING ON THE GROSS SKILLS AMONG CHILDREN AGED 10–12 YEARS-FOCUSED BOY STUDENTS - GRIVEDEHI, MOJTABA BRARARZADE; OZRUDI, MOHAMMADBAGHER FORGHANI; KHANJANI, MINA (Innovare Journal of Social Sciences, 2023)
The aim of this study is to examine the effect of 6 weeks of rope training on the gross skills among Children Aged 10–12 Years-Focused Boy Students. The study has been done in semi-experimental method. A recent study statistical society includes all boy students of elementary schools in which are learning Tanavarz National Project n in 117 schools in babul city. Statistical society has been selected randomly (cluster-stage) and in the first stage 3 schools and in the second stage in any school one class and in any class, about 18 students has been selected randomly and divided in three groups of control (n=15), fast (n=15) and demonstrations (n=15). Statistical datum has been analyzed by one-directed analysis and non-parametric test of Kruskal–Wallis and post-hoc test of Tukey by SPSS22 software and in the meaningful level of p≤0.05. Findings showed participants do have the mean height of 1.4±0.16 meter and the weight of 37.75±11.4 kg. Datum results showed Tanavarz Project from a statistical view in the two groups of fast and demonstrations does have a meaningful effect on balance, bilateral coordination, power, and growth of gross motor skills than to the control group. However, its effect on run speed and agility in the three groups were not meaningful. On the other hand, there is no meaningful difference among balance growth and two-directed coordination and the growth of gross motor skills in the group of fast-demonstrations Rope Training (p>0.05). Furthermore, there is the meaningful difference among the growth mean in children’s power in the group of fast-demonstrations Rope Training (p=0.001). On the other hand, fast Rope Training does have a meaningful improvement in children’s power growth in fast Rope Training to showing one. Rope Training could be a suitable program for the development of the gross motor skills of boys.